2014
DOI: 10.1055/s-0034-1375648
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability of GCKR Alters Lipid Profiles in Children with Monogenic and Autoimmune Diabetes

Abstract: Individuals who are homozygous TT at rs1260326 of the GCKR gene have higher triglyceride, total and LDL cholesterol levels regardless of the presence of GCK mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Here, we determined whether GCKR loci that were known to have significant associations with cholesterol and triglyceride levels in Korean adults [22] [26] and Caucasians with monogenic and autoimmune diabetes, regardless of GCKR mutations [27]. However, the association of GCKR variants, including rs780094, rs780092, and rs1260326, with triglycerides, a phenomenon that has been widely studied and replicated, was not detected in…”
Section: Discussionmentioning
confidence: 98%
“…Here, we determined whether GCKR loci that were known to have significant associations with cholesterol and triglyceride levels in Korean adults [22] [26] and Caucasians with monogenic and autoimmune diabetes, regardless of GCKR mutations [27]. However, the association of GCKR variants, including rs780094, rs780092, and rs1260326, with triglycerides, a phenomenon that has been widely studied and replicated, was not detected in…”
Section: Discussionmentioning
confidence: 98%
“…Several GWAS showed the association of GCKR variants primarily with serum TG level [15, 16, 19, 20, 22, 23, 26], moreover two of these GWAS and meta-analyses showed the association of the GCKR rs1260326 variant with plasma TC level [23, 26]. Homozygosity for the ‘T’ allele of rs1260320 was also shown to be associated with elevated TC and LDL-C levels in a Polish group of children with monogenic diabetes mellitus and type-1 diabetes mellitus [212]. In a Korean population-based candidate gene study, two other GCKR variants (rs780094 and rs780092) showed the association with TC level in adults and TC and LDL-C level in children [213].…”
Section: Genetic Basis Of Polygenic Hypercholesterolemia – the Genes mentioning
confidence: 99%